1993
DOI: 10.1136/vr.132.10.238
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible gastroenteritis in pigs in south east Spain: prevalence and factors associated with infection

Abstract: In the Murcia region of south east Spain, epidemics of transmissible gastroenteritis-like disease have occurred in pigs every three years since 1980. In 1987 a sero-epidemiological survey was conducted to estimate the prevalence and spread of transmissible gastroenteritis virus (TGEV) infection among breeding pigs and farms, and to determine any association between the infection and herd size and geographical zone. The Murcia region was divided into four geographical zones and the farms were classified by size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
17

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 0 publications
0
5
0
17
Order By: Relevance
“…In adult pigs and piglets greater than 3 weeks of age, the response to TGEV is milder, causing loss of appetite and diarrhea for 1 to 2 days [ 2 ]. TGEV was first reported in the United States in 1946 [ 3 ], and it was subsequently identified in Europe, Asia, Africa, and South America, causing heavy losses in the global pig breeding industry [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In adult pigs and piglets greater than 3 weeks of age, the response to TGEV is milder, causing loss of appetite and diarrhea for 1 to 2 days [ 2 ]. TGEV was first reported in the United States in 1946 [ 3 ], and it was subsequently identified in Europe, Asia, Africa, and South America, causing heavy losses in the global pig breeding industry [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the epidemic form, TGEV causes significant economic losses to the global pork industry 1–4 . In 1946, TGEV was first reported in the United States (US) 5 and was later identified in Europe (Belgium 6 , England 2 , France 7 , Germany 8 , The Netherlands 6 , and Spain 9 ), Asia (China 10 and Japan 11 ), Africa (South Africa 4 and Uganda 12 ), and South America (Brazil 13 ). Recent TGEV epidemiological studies are lacking in the US while sporadic outbreaks have been reported from China 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…TGE-CoV, which causes porcine transmissible gastroenteritis, was identified in the United States in 1945 [21]. Subsequently, the disease has been reported in many countries in Europe, Asia, Latin America and Africa [40][41][42][43][44][45][46]. TGE manifests as an epidemic of watery diarrhea with vomiting, rapidly spreading affecting virtually all pigs in contact within days [47,48].…”
Section: Transmissible Swine Gastroenteritis or Tgementioning
confidence: 99%